2016
DOI: 10.1200/jco.2015.61.4925
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Stereotactic Body Radiotherapy or Radiofrequency Ablation for Hepatocellular Carcinoma

Abstract: Data guiding selection of nonsurgical treatment of hepatocellular carcinoma (HCC) are lacking. We therefore compared outcomes between stereotactic body radiotherapy (SBRT) and radiofrequency ablation (RFA) for HCC. Patients and MethodsFrom 2004 to 2012, 224 patients with inoperable, nonmetastatic HCC underwent RFA (n = 161) to 249 tumors or image-guided SBRT (n = 63) to 83 tumors. We applied inverse probability of treatment weighting to adjust for imbalances in treatment assignment. Freedom from local progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
443
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 466 publications
(460 citation statements)
references
References 33 publications
(5 reference statements)
14
443
0
3
Order By: Relevance
“…Stereotactic body radiotherapy (SBRT) is an emerging radiotherapy technique that safely and effectively treats HCC by delivering large dose of radiation (6–15 Gy per fraction, as used in our RT/IL-12 protocol) to liver tumors in 1–6 fractions. 45 SBRT is believed to achieve tumor control via its effects on vascular, stromal and immunological aspects of the tumor microenvironment. 46 The early clinical success of combining RT with systemic therapy to treat advanced HCC marks the promise of RT-containing multimodality protocols for this dismal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) is an emerging radiotherapy technique that safely and effectively treats HCC by delivering large dose of radiation (6–15 Gy per fraction, as used in our RT/IL-12 protocol) to liver tumors in 1–6 fractions. 45 SBRT is believed to achieve tumor control via its effects on vascular, stromal and immunological aspects of the tumor microenvironment. 46 The early clinical success of combining RT with systemic therapy to treat advanced HCC marks the promise of RT-containing multimodality protocols for this dismal disease.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT matching has been suggested to be superior to orthogonal x-rays 56 . The use of peri-tumoral fiducials, with both x-rays and CBCT can further enhance set-up 21,26,31,32,34,52,57 . The presence of lipiodal following TACE, or surgical clips, have also been used as surrogates for tumour position 21,26 .…”
Section: Image Guidancementioning
confidence: 99%
“…A recent retrospective study of 224 patients from the University of Michigan compared outcomes in patients undergoing either RFA or SBRT. The authors reported that while local control did not vary with tumor size for SBRT, lesions greater than 2 cm in maximal diameter had worse local control when treated with RFA (13). On multivariate analysis, RFA was associated with a hazard ratio of 3.84 (P=0.002) for local progression when compared to SBRT, and overall rates of local progression were higher with RFA.…”
Section: Unresectable Hccmentioning
confidence: 86%